Here u is general, so consider it to be just a function of x. u=u(x). del(u(x))= u1(x)-u(x). u1(x) represents any varied function. Now, d/dx(u(x))=d/dx(u1(x)-u(x))=[d/dx(u1(x))-d/dx(u(x))]=u1'(x)-u'(x). But u1 is any general varied function so is u1'. So, u1'(x)-u'(x)=del(u') ----(1). So, alpha*v'=del(u').
Great Explanation !!!
How is alpha*(v_dash)=del u_dash ?
Here u is general, so consider it to be just a function of x. u=u(x). del(u(x))= u1(x)-u(x). u1(x) represents any varied function. Now, d/dx(u(x))=d/dx(u1(x)-u(x))=[d/dx(u1(x))-d/dx(u(x))]=u1'(x)-u'(x). But u1 is any general varied function so is u1'. So, u1'(x)-u'(x)=del(u') ----(1). So, alpha*v'=del(u').
Bro, if u got to know why?, please comment or please tell which book to refer
Thanks a lot sirrr